2008
DOI: 10.1186/1476-069x-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Control of asthma triggers in indoor air with air cleaners: a modeling analysis

Abstract: Background: Reducing exposure to environmental agents indoors shown to increase asthma symptoms or lead to asthma exacerbations is an important component of a strategy to manage asthma for individuals. Numerous investigations have demonstrated that portable air cleaning devices can reduce concentrations of asthma triggers in indoor air; however, their benefits for breathing problems have not always been reproducible. The potential exposure benefits of whole house high efficiency in-duct air cleaners for sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 56 publications
2
43
0
Order By: Relevance
“…The mean estimated ETS-PM concentration of 16 mg/m 3 for exposed households in our study falls on the lower side of the range of concentrations measured in previous large-scale residential ETS studies (Dockery and Spengler, 1981;Leaderer, 1990;Ozkaynak et al, 1996). Our results are also in agreement with recent modeling studies: Klepeis et al reported means ranging from 6.6-49 mg/m 3 from multiple simulations using a simple box model approach; and Myatt et al reported a mean of 15 mg/m 3 and a median of 17.8 mg/m 3 using the CONTAM model (Klepeis and Nazaroff, 2006;Myatt et al, 2008). These studies incorporated time-activity patterns and ventilation patterns but relied on a hypothetical smoking population, whereas our study is a snapshot characterization of equilibrium concentrations based on parameters estimated from a national survey.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mean estimated ETS-PM concentration of 16 mg/m 3 for exposed households in our study falls on the lower side of the range of concentrations measured in previous large-scale residential ETS studies (Dockery and Spengler, 1981;Leaderer, 1990;Ozkaynak et al, 1996). Our results are also in agreement with recent modeling studies: Klepeis et al reported means ranging from 6.6-49 mg/m 3 from multiple simulations using a simple box model approach; and Myatt et al reported a mean of 15 mg/m 3 and a median of 17.8 mg/m 3 using the CONTAM model (Klepeis and Nazaroff, 2006;Myatt et al, 2008). These studies incorporated time-activity patterns and ventilation patterns but relied on a hypothetical smoking population, whereas our study is a snapshot characterization of equilibrium concentrations based on parameters estimated from a national survey.…”
Section: Discussionsupporting
confidence: 93%
“…Given increasing smoking restrictions in public places, the majority of the exposure and risk burden may shift to the residential environment, but no study to date has developed broad-based and generalizable models of ETS exposure inside homes. Previous residential studies have either characterized ETS contributions to residential exposures within hypothetical simulation models or using measurements but without a nationally generalizable model framework (Dockery and Spengler, 1981;Leaderer, 1990;Ozkaynak et al, 1996;Klepeis and Nazaroff, 2006;Myatt et al, 2008). It is therefore unknown how variability in smoking patterns correlates with housing characteristics that influence indoor concentrations of ETS, necessary in determining variability in residential concentrations and risk.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile air cleaners can run on various technologies (Berenjian et al 2012;Zhang et al 2011). Many studies have been published about investigations on air cleaners for particle (Chan and Cheng 2006;Jaworek et al 2007;Mølgaard et al 2014;Myatt et al 2008;Novoselac and Siegel 2009;Ongwandee and Kruewan 2013) or allergen (Reisman 2001) filtration. Particle filters usually contain paper or textile materials but are ineffective against gaseous pollutants.…”
Section: Responsible Editor: Constantini Samaramentioning
confidence: 99%
“…The CONTAM multi-zone indoor air quality model (Walton and Dols, 2003) developed by the National Institute of Standards and Technology (NIST) was used to estimate indoor radon concentrations following a previously published methodology (Myatt et al, 2008;MacIntosh et al, 2009). Briefly, airflow among indoor and outdoor zones of the building (that is, rooms and ambient air) in CONTAM occurs through flow paths such as doors, windows, and cracks.…”
Section: Exposure Modelingmentioning
confidence: 99%